The Influence of Process Ease and Service Satisfaction on Student Payment Compliance: Evidence from a Private University in Surabaya - Winarto Poernomo (STIE AMKOP, 2025)
Student decisions in higher education are influenced not only by academic quality but also by how smooth administrative services are and how simple admission procedures feel. Although many students report that services are satisfactory and registration is convenient, it is unclear whether these perceptions directly affect their willingness to pay tuition fees. This research explores how service satisfaction and process ease relate to payment compliance at a private university in Surabaya, Indonesia. The institution enrolls about 6,157 students and charges an average tuition fee of thirty million rupiah per semester. Data were obtained from 2,646 survey responses and analyzed using chi-square tests and logistic regression to examine the link between perceptions and payment outcomes. Results show that even though most respondents evaluated services and processes positively, neither factor demonstrated a significant statistical effect on tuition compliance. These findings suggest that financial ability and external economic pressures may play a stronger role than service perceptions. The study contributes by distinguishing between satisfaction with enrollment procedures and actual financial commitment, offering both theoretical insights and managerial implications for higher education institutions.